Strain and elasticity imaging in compression optical coherence elastography: The two‐decade perspective and recent advances. Issue 2 (3rd November 2020) - Zaitsev, Vladimir Y.; Matveyev, Alexander L.; Matveev, Lev A.; Sovetsky, Alexander A.; Hepburn, Matt S.; Mowla, Alireza; Kennedy, Brendan F.
Abstract: Quantitative mapping of deformation and elasticity in optical coherence tomography has attracted much attention of researchers during the last two decades. However, despite intense effort it took 15 years to demonstrate optical coherence elastography (OCE) as a practically useful technique. Similarly to medical ultrasound, where elastography was first realized using the quasi‐static compression principle and later shear‐wave‐based systems were developed, in OCE these two approaches also developed in parallel. However, although the compression OCE (C‐OCE) was proposed historically earlier in the seminal paper by J. Schmitt in 1998, breakthroughs in quantitative mapping of genuine local strains and the Young's modulus in C‐OCE have been reported only recently and have not yet obtained sufficient attention in reviews. In this overview, we focus on underlying principles of C‐OCE; discuss various practical challenges in its realization and present examples of biomedical applications of C‐OCE. The figure demonstrates OCE‐visualization of complex transient strains in a corneal sample heated by an infrared laser beam. Abstract : In this paper we present the two‐decade perspective of the development of quantitative mapping of deformation and elasticity based on the idea of Compression Optical Coherence Elastography (C‐OCE). Despite intense effort, breakthroughs in practically useful realizations of C‐OCE were reported only recently and have not yet obtained due attention in reviews. Here, we focus on underlying principles of C‐OCE, discuss practical challenges in its realization and present examples of various biomedical applications of C‐OCE.